2001
DOI: 10.1001/archpedi.155.12.1340
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oral or Nebulized Dexamethasone for Children With Mild Croup

Abstract: Children with mild croup who receive oral dexamethasone treatment are less likely to seek subsequent medical care and demonstrate more rapid symptom resolution compared with children who receive nebulized dexamethasone or placebo treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…It is presumed that corticosteroids possess rapidly acting anti‐inflammatory or vasoconstrictive properties in the upper airway 8 , 14 , 19 . Studies using oral dexamethasone, 21 , 23 , 25 nebulised budesonide (2 mg/dose) 15 , 18 and nebulised dexamethasone 26 have demonstrated the efficacy of corticosteroids compared with placebo in relieving croup symptoms in the hospital setting. Commonly used alternatives to dexamethasone are prednisone or prednisolone 6 , 16 …”
Section: Evidence‐based Treatment Optionsmentioning
confidence: 99%
“…It is presumed that corticosteroids possess rapidly acting anti‐inflammatory or vasoconstrictive properties in the upper airway 8 , 14 , 19 . Studies using oral dexamethasone, 21 , 23 , 25 nebulised budesonide (2 mg/dose) 15 , 18 and nebulised dexamethasone 26 have demonstrated the efficacy of corticosteroids compared with placebo in relieving croup symptoms in the hospital setting. Commonly used alternatives to dexamethasone are prednisone or prednisolone 6 , 16 …”
Section: Evidence‐based Treatment Optionsmentioning
confidence: 99%
“…8,9 Only two published trials have focused on corticosteroid treatment of mild croup. 10,11 One did not use clinical criteria to define mild croup clearly, 10 and the other included children with audible stridor at rest and indrawing of the chest wall, 11 symptoms that most health care professionals consider to represent more severe disease. The first study was small (100 patients) and assessed only one outcome: return to medical care for croup.…”
mentioning
confidence: 99%
“…They found that a single dose of oral dexamethasone (0.6 mg/kg/dose, maximum 20 mg) resulted in a significantly quicker resolution of symptoms and improvement in croup score compared to placebo [92]. Additional studies have consistently shown that GCs improve croup symptoms scores and reduce hospital admissions [57, 9294]. In addition, a recent cochrane review of 38 RCTs, with a total of 4299 children pooled, further confirmed that GCs are effective in improving croup score symptoms and decreasing the number of return visits, (re)admissions, and hospital length of stay [57].…”
Section: Clinical Evidence Of the Use Of α-Ar Agonists And Gc In Tmentioning
confidence: 99%
“…Oral dexamethasone (0.6 mg/kg/dose) has been found to be as effective as intramuscular dexamethasone [94], and both are superior to nebulized dexamethasone in the treatment of mild and moderately severe croup in children [95]. Interestingly, high-dose nebulized budesonide (2–4 mg) seems to be equally effective as either oral or intramuscular dexamethasone in treatment of croup [9698].…”
Section: Clinical Evidence Of the Use Of α-Ar Agonists And Gc In Tmentioning
confidence: 99%